Exceptional Powers. Suspending and Limiting Constitutional Rights. On the Constitutional Court Sentence 148/2021, of July 14. - Ródenas Calatayud, Ángeles; Ruiz Manero, Juan (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
Constitutional Court Sentence 148/2021, of July 14, made a drastic modification in the configuration of the power to declare a state of alarm with respect to its original conformation by the organic legislator. In order to examine this, the authors begin by setting out the different arguments of the Constitutional Court in the aforementioned sentence, linking each of them to each of the requirements of the power conferring rule to declare a state of alarm. The heart of the Constitutional Court’s arguments lies in the requirement of material competence. The authors critically analyze the aforementioned sentence, focusing basically on the difference between limiting and suspending a constitutional right, which in turn constitutes the cornerstone of the Constitutional Court argumentation. In the authors’ opinion, the declaration of the state of alarm by the Council of Ministers on March14 was perfectly constitutional, since it fits with what would be an adequate reconstruction of what a limitation of a constitutional right entails.